[PP.25.07] EVOLUTION OF COMPUTED TOMOGRAPHY-DETECTABLE ADRENAL NODULES IN PATIENTS WITH BILATERAL PRIMARY ALDOSTERONISM. (September 2016) - Mulatero, P.; Burrello, J.; Lucatello, B.; Monticone, S.; Giacchetti, G.; Ronconi, V.; Battocchio, M.; Fallo, F.
Abstract : Objective: Idiopatic hyperaldosteronism (IHA) due to bilateral production of aldosterone (bilateral PA) is the most common subtype of primary aldosteronism (PA). Adrenal CT scanning in PA patients can show normal to bilateral diffuse enlargement or nodular glands. Natural course of adrenal mass lesions in IHA patients has not yet been fully clarified. The aim of our study was to assess the over time evolution of CT-detectable adrenal nodule(s) in patients with IHA. Design and method: Thirty-two patients diagnosed as IHA during the last 6 years were recruited on the basis of their medical records, indicating the presence of nodular adrenal lesions at adrenal CT scanning. Results: Thirty-two patients (23 males and 9 females; age 50 ± 9 years) were included in the study. The median diameter of the adrenal nodules was 12 mm, range 8 to 28 mm; 28 patients had unilateral lesions and 4 had bilateral nodules. Adrenal was described as nodular when unilateral or bilateral nodule(s) of at least 8 mm in diameter were detected using CT with contrast and fine cuts. The diagnosis of a benign adrenal nodule rested on the following CT criteria: size <4 cm, regular shape with well-defined margins, homogeneous and hypodense content. All patients had CT imaging re-evaluated 3 to 6 years (median 45 months) after diagnosis. A unilateral nodular lesion enlargement greater or equal than 25% was detected in 2 cases; a slight increase (<25%) or no variations or a decrease of nodule size occurred in the remaining 30 cases. No patients showed appearance of radiological picture of malignancy or new masses in the ipsilateral/contralateral glands. At follow-up all patients reported compliance to medications, and 29/32 patients had a persistent clinical/biochemical control of the disease. Three patients showed hypertension resistant to a combination of four different antihypertensive drugs. Conclusions: Over time CT variations of adrenal nodules are uncommon and without apparent signs of malignancy in patients with AVS-confirmed bilateral PA. A diagnostic reassessment may be advisable in patients with marked changes in adrenal morphology and/or resistant hypertension.